Spatial Distribution of Educational, Health, and Security Services Using GIS (The Andalusia District Municipality as a Model) "A Study in Services Geography" (Al-Jabal Journal of Humanities and Applied Sciences, 2024)
The municipality of Hay Al-Andalus is considered within the scope of the city of Tripoli in the West, and it is one of the residential neighborhoods located in the Libyan capital. It is bordered to the west by Qarqarash, to the east by Tripoli, the center, to the north by the Mediterranean Sea, and to the south by Qarji. It is considered the most crowded municipality of Tripoli in terms of population, and the shops that belong to the municipality. The Andalus district is: Qarqarash locality, Al-Madinah Al-Siyahiyya locality, Qarji Al-Tadamon locality, Qurtuba locality, Al-Daribi locality, Al-Sarraj Al-Sharqiya locality, Al-Hay Al-Sinaiya locality, Al-Salam North Western Street locality, Ghout Al-Shaal (Al-Qadisiyah) locality, Ghout Al-Shaal (Al-Istiklal) locality, Al-Muhandisin neighborhood, Al-Toghar neighborhood, Al-Andalus neighborhood neighborhood, Al-Markaz neighborhood, Al-Kabeer Street neighborhood, Southern Western Street neighborhood, Ghout Al-Shaal (Al-Wakim) neighborhood. This research aims to shed light on the spatial distribution of educational, health, and security services using the GIS program. The study relied on the descriptive, analytical, and interpretive approach to this distribution using a set of maps.
Keywords: geography of services, geographic information systems, municipality, demographics